2019
DOI: 10.1016/j.rser.2018.12.020
|View full text |Cite
|
Sign up to set email alerts
|

Integrated decision-support methodology for combined centralized-decentralized waste-to-energy management systems design

Abstract: The rapid expansion of urban populations and concomitant increase in the generation of municipal solid waste (MSW) exert considerable pressure on the conventional centralized MSW management system and are beginning to exceed disposal capacities. To tackle this issue, the conventional centralized MSW management system is more likely to evolve toward a more decentralized system with smaller capacity waste treatment facilities that are integrated at different levels of the urban environment, e.g., buildings, dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(24 citation statements)
references
References 41 publications
(39 reference statements)
0
22
0
2
Order By: Relevance
“…This creates important challenges from computational design and managerial standpoints (Cardin et al 2017). Our research focuses on developing the computational tools, digital processes, stochastic optimisation, and machine learning algorithms that will support better design and decision-making in such a deeply uncertain, and heavily data-driven environment (de Neufville et al 2019;Kuznetsova et al 2019).…”
Section: Data-driven Systems Engineeringmentioning
confidence: 99%
“…This creates important challenges from computational design and managerial standpoints (Cardin et al 2017). Our research focuses on developing the computational tools, digital processes, stochastic optimisation, and machine learning algorithms that will support better design and decision-making in such a deeply uncertain, and heavily data-driven environment (de Neufville et al 2019;Kuznetsova et al 2019).…”
Section: Data-driven Systems Engineeringmentioning
confidence: 99%
“…The model indicated a wide range of optimal UV dose ratios while comparing reactor design. Kuznetsova, Cardin, Diao, and Zhang (2019) conducted a modified decision support methodology to analyze municipal solid waste generation and optimize a multi-level urban waste management system that combines centralized and decentralized facilities. They found that the proposed adjustments, assessed in a case study in Singapore, reduced operational costs, and increased revenue from energy recovery while allowing for more efficient land use and a reduction in transportation requirements.…”
Section: Modelingmentioning
confidence: 99%
“…The government should solve problems such as inadequate preplanning, insufficient funds, sparse site space, and nonconforming existing facilities to provide more available supporting infrastructure. On the one hand, the planning, construction, and operation of the supporting infrastructure should be carried out simultaneously with the main WTE project while adhering to environmental criteria and technical requirements to avoid secondary pollution . On the other hand, the government should fully take into consideration the funds and land space for a supporting infrastructure during the planning phase.…”
Section: Practical and Managerial Implicationsmentioning
confidence: 99%